Role of Clinical Pharmacist in Improving Mental Health Literacy among Adolescents - Jayaram, Logarjuna; Nagaraju, Kiran (Indian Journal of Pharmacy Practice)
Adolescence is a critical period for mental health development, yet mental health literacy among these demographic remains alarmingly low. This article explores the pivotal role of clinical pharmacists in improving mental health literacy among adolescents. It begins by defining mental health literacy and outlining the current challenges, including stigma, misinformation and a lack of resources. The evolving role of clinical pharmacists in mental health care is examined, emphasizing their unique position to educate and support adolescents. Through pharmacist-led educational programs, counselling services and community outreach, clinical pharmacists can significantly enhance adolescents' understanding of mental health issues, leading to improved treatment adherence and better long-term mental health outcomes. The article also highlights the challenges faced by clinical pharmacists and identifies opportunities for expanding their role in mental health care. The conclusion calls for greater integration of clinical pharmacists into mental health literacy programs and suggests areas for future research and practice development.
Keywords: Clinical Pharmacist; Mental Health Literacy; Adolescents; Mental Health Education; Stigma Reduction